Estudo computacional de monocamadas de C, Si, Ge e suas ligas binárias - Kremer, Luiz Felipe (2022)
Whitin the framework of the density funcional theory, we performed first principles calculations on the main properties (geometry and electronic) of group IV monolayers. The first studied system was the presence of carbon and silicon nanodomains in a monolayer of silicon carbide (SiC). We found that nanodomains alter the electronic properties of the SiC monolayer, changing its energy gap. Moreover, in the presence of nanodomains, the energy adsorption of H2 and O2 is in the range of the optimal values for hydrogen storage. Next, we studied non hidrogenated 2D nanodomains in a hidrogenated SiC monolayer (H-SiC). These nanodomains act as quantum dots (QD) and lead the H-SiC to present optical absorption in the visible reagion. In addition, depending of the geometry of the QD, the system can present a magnetization of 1 for each unpared atom. Finaly, we studied porous monolayers in the graphenylene symmetry. We found that the graphenylene and SiC and GeC (in the graphenylene symmetry) present energy gaps of 0.067 eV, 1.94 eV and 1.59 eV, respectively. Moreover, we analized the possibility to use these structures for hydrogen evolution reaction (HER), to do this we calculated the free Gibbs adsorption energies of the structures with adsorbed hydrogen atom. We found that the Ge present the best value with 0.101 eV, being comparable to Pt (the standard material for HER). Also, we calculated the adsorption energy of the H2 molecule. The results show that the adsorption energies are in the optimal region for hydrogen storage. These results can be used to elucidate the possible applications of the studied nanostructures.